Robust memory humoral immune response to SARS-CoV-2 in the tonsils of adults and children - Altorki, Tarfa A.; Abdulal, Rwaa H.; Suliman, Bandar A.; Aljeraisi, Talal M.; Alsharef, Asem; Abdulaal, Wesam H.; Alfaleh, Mohamed A.; Algaissi, Abdullah A.; Alhabbab, Rowa Y.; Ozbak, Hani; Eid, Hamza Mohammed; Almutawif, Yahya Ahmad; et al. (Frontiers in Immunology, 2023)
Background: Adaptive humoral immunity against SARS-CoV-2 has mainly been evaluated in peripheral blood. Human secondary lymphoid tissues (such as tonsils) contain large numbers of plasma cells which secrete immunoglobulins at mucosal sites. Yet, the role of mucosal memory immunity induced by vaccines or natural infection against SARS-CoV-2 and its variants is not fully understood.Methods: Tonsillar mononuclear cells (TMNCs) from adults (n=10) and children (n=11) were isolated and stimulated using positive SARS-CoV-2 nasal swabs. We used endpoint ELISA for the measurement of anti-S1, -RBD and -N IgG antibodies levels and pseudovirus microneutralization assay to assess neutralizing antibodies (nAbs) in paired serum and supernatants from stimulated TMNCs.Strong systemic humoral response in previously SARS-CoV-2 infected and vaccinated adults and children was observed in accordance with the reported history of the participants. Interestingly, we found a significant increase in anti-RBD IgG (305 and 834 folds) and anti-S1 IgG (475 and 443 folds) in stimulated TMNCs from adults and children, respectively, compared to unstimulated cells. Consistently, simulated TMNCs secreted higher levels of nAbs against ancestral Wuhan strain and Omicron BA.1 variant compared to unstimulated cells by several folds. This increase was seen in all participants including children with no known history of infection, suggesting that these participants might have been previously exposed to SARS-CoV-2 and that not all asymptomatic cases necessarily could be detected by serum antibodies. Furthermore, nAb levels against both strains were significantly correlated 4 in adults (r=0.8788; p = 0.0008) and children (r = 0.7521; p = 0.0076), and they strongly correlated with S1 and RBD-specific IgG antibodies.Our results provide evidence for persistent mucosal humoral memory in tonsils from previously-infected and/or vaccinated adults and children against recent and old variants upon re-exposure. They also highlight the importance of targeting mucosal sites by vaccines to help controlling infection at the primary sites and preventing potential breakthrough infections.